A flame retardant and anti-aging cable material and preparation method thereof

By using modified carbon nanotubes and composite fillers in cable materials, the shortcomings of existing cable materials in flame retardant, mechanical properties and anti-aging properties are solved, and the excellent performance and long-term flame retardant effect of the material are achieved.

CN119410043BActive Publication Date: 2025-04-15YANCHENG JINGZE NEW MATERIAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510018229.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

Existing cable materials have shortcomings in flame retardant, mechanical properties and anti-aging properties, especially when inorganic fillers are added directly, they are prone to aggregation and difficult to disperse, resulting in a degradation of performance.

Method used

The mechanical properties, flame retardant properties and anti-aging properties of cable materials are improved by adding modified carbon nanotubes and composite fillers. Modified carbon nanotubes are made of chemically modified flame retardant and para-phenylenediamine to increase their dispersion and binding force in cable materials; composite fillers improve the mechanical properties and anti-aging ability of the material through the synergistic action of titanium dioxide nanosheets and silica nanoparticles.

Benefits of technology

The excellent mechanical properties, good flame retardant properties and significant anti-aging properties of cable materials are achieved, and performance defects caused by the aggregation of inorganic fillers are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of cable materials, and discloses a flame-retardant and anti-aging cable material and a preparation method thereof. The flame-retardant and anti-aging cable material comprises the following components in parts by weight: 45-70 parts of nitrile rubber, 20-40 parts of natural rubber, 7-12 parts of modified carbon nanotubes, 5-10 parts of composite fillers, 3-5 parts of nano zinc oxide, 2-4 parts of stearic acid, 1-3 parts of sulfur, and 0.1-0.5 parts of accelerators; the modified carbon nanotubes are prepared by modifying flame retardants and p-phenylenediamine on the surfaces of the carbon nanotubes by chemical reactions; the composite fillers are prepared by in-situ growing silicon dioxide nanoparticles by using titanium dioxide nanosheets as carriers. The invention provides the cable material with excellent mechanical properties, flame retardant properties and anti-aging properties by adding the modified carbon nanotubes and the composite fillers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cable materials, and in particular relates to a flame retardant and anti-aging cable material and a preparation method thereof. Background Art

[0002] Cable material is a polymer material used for insulation and protection of wires and cables, mainly divided into rubber, plastic, nylon and other categories. Currently, the two major organic polymer materials used to prepare cable insulation materials are plastic and rubber. Among them, plastics such as polyvinyl chloride plastics and cross-linked polyethylene plastics have poor flame retardant properties; rubbers such as ethylene propylene rubber and silicone rubber have average flame retardant and mechanical properties.

[0003] In addition, in the actual production process, cable materials will be used in conjunction with a large amount of inorganic fillers (such as inorganic reinforcing agents, inorganic flame retardants, etc.), thereby changing the vulcanization properties, physical and mechanical properties and thermal properties of the rubber. However, there are two disadvantages when inorganic fillers are directly added to the rubber: First, the surface energy of the inorganic filler particles is high and they are in a thermodynamically unstable state, and they are very easy to aggregate into agglomerates, which directly affects the application effect of the inorganic filler particles; second, the surface of the inorganic filler particles is hydrophilic and oleophobic, with strong polarity, making it difficult to disperse evenly in the rubber, and the bonding force between the inorganic filler particles and the rubber is weak, resulting in interface defects, which leads to a decrease in the performance of the cable sheath material. In addition, since the cable is used outdoors for a long time and is subjected to heat, oxygen aging and ultraviolet radiation, it is easy to cause aging and degradation. Summary of the invention

[0004] In order to solve the deficiencies mentioned in the above background technology, the purpose of the present invention is to provide a flame retardant and anti-aging cable material and a preparation method thereof, and to give the cable material excellent mechanical properties, flame retardant properties and anti-aging properties by adding modified carbon nanotubes and composite fillers.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A flame retardant and anti-aging cable material, comprising the following components in parts by weight: 45-70 parts of nitrile rubber, 20-40 parts of natural rubber, 7-12 parts of modified carbon nanotubes, 5-10 parts of composite fillers, 3-5 parts of nano zinc oxide, 2-4 parts of stearic acid, 1-3 parts of sulfur, and 0.1-0.5 parts of accelerator;

[0007] The modified carbon nanotubes are prepared by modifying the flame retardant and p-phenylenediamine on the surface of the carbon nanotubes by chemical reaction. The structural formula of the flame retardant is as follows:

[0008]

[0009] The composite filler is made by in-situ growing silicon dioxide nanoparticles using titanium dioxide nanosheets as carriers.

[0010] Preferably, the accelerator is one of DM, M, TMTD and D, or a mixture of several of them.

[0011] Preferably, the method for preparing the modified carbon nanotubes comprises the following steps:

[0012] A. Put concentrated sulfuric acid and concentrated nitric acid in a reactor, add carbon nanotubes, disperse them evenly with ultrasound, place them at 50-70°C and stir for 4-6 hours, filter, wash and dry after the reaction is completed to obtain acidified carbon nanotubes;

[0013] B. Take the acidified carbon nanotubes in anhydrous butyl acetate, disperse them uniformly by ultrasonication, raise the temperature to 60-70°C, add the mixture of flame retardant and anhydrous butyl acetate and dibutyltin dilaurate, react at constant temperature for 8-12 hours, filter, wash and dry after the reaction is completed to obtain a modified intermediate;

[0014] C. Take the modified intermediate and disperse it in N, N-dimethylacetamide by ultrasonic. Add dichlorothionyl and reflux it at 75-85°C for 18-24 hours. Then add p-phenylenediamine and reflux it at 120-135°C for 24-48 hours under nitrogen protection. After the reaction is completed, filter, wash and dry to obtain modified carbon nanotubes.

[0015] Preferably, in step B, the mass ratio of the acidified carbon nanotubes to the flame retardant is 1:2-3.

[0016] Preferably, in step C, the addition ratio of the modified intermediate, thionyl chloride and p-phenylenediamine is 1-5 g: 30-70 mL: 3-5 g.

[0017] Preferably, the structural formula of the flame retardant in step B is as follows:

[0018]

[0019] The preparation method comprises the following steps:

[0020] B1. Put vanillin and anhydrous potassium carbonate into a reactor filled with tetrahydrofuran, stir to dissolve, then add hexachlorocyclotriphosphazene, react at 65-80°C for 42-48h, filter after the reaction is completed, collect the filtrate, evaporate the solvent, wash with ethanol, and vacuum dry to obtain component 1;

[0021] B2, take ethanolamine and ethanol into a reactor, add component one, place under reflux reaction at 75-90°C for 12-24h, cool to room temperature after the reaction is completed, filter and dry the solid to obtain component two;

[0022] B3. Take isophorone diisocyanate in a reactor, add anhydrous butyl acetate and dibutyltin dilaurate, raise the temperature to 40-55°C, add component 2 and stir to react for 5-8 hours to obtain a flame retardant.

[0023] Preferably, in step B2, the molar ratio of ethanolamine to component 1 is 6.6-10:1.

[0024] Preferably, in step B3, the molar ratio of isophorone diisocyanate to component 2 is 1-2:1.

[0025] Preferably, the method for preparing the composite filler comprises the following steps:

[0026] (1) Tetrabutyl titanate is placed in a reactor, hydrofluoric acid is added, stirred and mixed, and reacted at 195-210° C. for 18-24 hours. After the reaction is completed, the reaction is filtered, washed and dried to obtain titanium dioxide nanosheets;

[0027] (2) Put titanium dioxide nanosheets in a reactor, add a mixture of ethanol and deionized water, disperse them evenly by ultrasonication, add γ-aminopropyltriethoxysilane, and reflux them at 70-85°C in a nitrogen atmosphere for 5-7 hours. After the reaction is completed, filter, wash, and dry to obtain amino titanium dioxide nanosheets;

[0028] (3) Aminated titanium dioxide nanosheets are ultrasonically dispersed in a 1.5-2 mol / L citric acid solution to obtain a dispersion. Water glass is added to deionized water and mixed. Then, ethanol is added and stirred evenly. The temperature is raised to 75-85°C, the obtained dispersion is added, and a dilute sulfuric acid solution is added dropwise to adjust the pH of the system to 5-6. Ethanol is added and the reaction is stopped when the reaction temperature is maintained at 75-85°C. After the reaction is completed, the composite filler is aged, centrifuged, washed, and dried to obtain the composite filler.

[0029] Preferably, the method for preparing the flame retardant and anti-aging cable material as described above comprises the following steps:

[0030] S1. Weigh each raw material by weight, put the nitrile rubber and natural rubber into an internal mixer and plasticize for 2-3 minutes to obtain a premix;

[0031] S2. Add modified carbon nanotubes, composite fillers, nano zinc oxide and stearic acid to the premix and mix for 3 to 5 minutes. Finally, add sulfur and accelerator and mix evenly. Vulcanize at 120 to 160°C for 5 to 10 minutes. Cool the premix to obtain a flame retardant and anti-aging cable material.

[0032] Beneficial effects of the present invention:

[0033] The invention uses hexachlorocyclotriphosphazene, vanillin, ethanolamine and isophorone diisocyanate as raw materials to synthesize a novel flame retardant, wherein the isocyanate group directly connected to the cyclohexane ring in the isophorone diisocyanate has high reaction activity and first reacts with the hydroxyl group on the surface of the second component, thereby introducing the isocyanate group on the surface of the flame retardant, and then the flame retardant reacts with the acidified carbon nanotubes, the surface of the carbon nanotubes after the acidification treatment is rich in hydroxyl groups and carboxyl groups, the isocyanate group in the flame retardant structure reacts with the hydroxyl group on the surface of the acidified carbon nanotubes to obtain a modified intermediate, thereby introducing the isocyanate group on the surface of the carbon nanotubes. The surface is modified with flame retardants, which can not only play a good flame retardant effect, but also does not have the problem of migration and seepage, ensuring that the cable material achieves a long-term flame retardant effect. In addition, the carboxyl groups on the surface of the modified intermediate are chlorinated and then grafted with the antioxidant p-phenylenediamine. Due to the tubular structure of carbon nanotubes, the antioxidant can be slowly released, thereby limiting the migration of the antioxidant in the matrix. At the same time, after the carbon nanotubes are surface modified with flame retardants and antioxidants, the surface lipophilicity of the carbon nanotubes is improved, which makes the carbon nanotubes relatively evenly dispersed in the matrix, avoiding the performance defects caused by carbon nanotube agglomeration to a certain extent.

[0034] The present invention uses titanium dioxide nanosheets with a large surface area as a carrier, uses γ-aminopropyltriethoxysilane to introduce reaction sites on the surface of the titanium dioxide nanosheet, and then grows silicon dioxide nanoparticles in situ on the surface of the titanium dioxide nanosheet by an electrostatic assembly method to prepare a composite filler. Titanium dioxide and silicon dioxide work synergistically to promote the dispersion of the composite filler in the matrix and improve the mechanical properties of the cable material. Moreover, nano titanium dioxide, as an important inorganic ultraviolet shielding agent, can reduce ultraviolet light aging and has spectral antibacterial, deodorizing, mildew-proof and other effects. In addition, during the stretching process, the rubber molecular chain will produce a slip phenomenon along the orientation of the titanium dioxide nanosheet, thereby promoting the dispersion of stress and further improving the mechanical properties of the cable material. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] In the embodiments of the present invention and the comparative examples, the carbon nanotubes have a diameter of 45-65 nm and a length of 6-16 μm, and are produced by Shenzhen Nanoport Co., Ltd.; nitrile rubber (NBR1704) is produced by Zhenjiang Nandi Chemical Co., Ltd., with an acrylonitrile content of 19%; natural rubber grade SCR20 is produced by Sanlishi Co., Ltd.; the particle size of nano zinc oxide is 20-30 nm, and is produced by Shaoxing Amico New Materials Technology Co., Ltd.; the particle size of nano titanium dioxide in comparative example 5 is 15-20 nm, and is produced by Xi'an Chuangjie Environmental Technology Co., Ltd.; the average particle size of nano silicon dioxide is 15 nm, and is produced by Jiangsu Lianyungang Pengrui Chemical Co., Ltd.

[0037] Example 1 A method for preparing modified carbon nanotubes comprises the following steps:

[0038] A. Take 300 mL of concentrated sulfuric acid and 100 mL of concentrated nitric acid in a reactor, add 5 g of carbon nanotubes, disperse evenly by ultrasonication, place at 65 ° C and stir for 4 h, filter, wash and dry after the reaction is completed to obtain acidified carbon nanotubes;

[0039] B. Take 5g of acidified carbon nanotubes in 120mL of anhydrous butyl acetate, disperse them evenly by ultrasonication, heat to 65°C, add a mixture of 12.2g of flame retardant and 60mL of anhydrous butyl acetate, and 0.03g of dibutyltin dilaurate, react at constant temperature for 12h, filter, wash and dry after the reaction is completed to obtain a modified intermediate;

[0040] C. Take 5 g of the modified intermediate and disperse it in 200 mL of N, N-dimethylacetamide by ultrasonic. Add 60 mL of dichlorothionyl and reflux at 80 ° C for 24 h. Then add 4.4 g of p-phenylenediamine and reflux at 125 ° C for 36 h under nitrogen protection. After the reaction is completed, filter, wash and dry to obtain modified carbon nanotubes.

[0041] The preparation method of the flame retardant in step B comprises the following steps:

[0042] B1, take 19.2g of vanillin and 17.8g of anhydrous potassium carbonate and put them into a reactor filled with 300mL of tetrahydrofuran, stir and dissolve, then add 5g of hexachlorocyclotriphosphazene, place at 75°C for reaction for 48h, filter after the reaction is completed, collect the filtrate, evaporate the solvent and wash with ethanol, and vacuum dry to obtain component 1;

[0043] B2, take 4.27g ethanolamine and 80mL ethanol in a reactor, add 10.4g component one, place under reflux reaction at 85°C for 18h, cool to room temperature after the reaction is completed, filter and dry the solid to obtain component two;

[0044] B3. Take 13.2 g of isophorone diisocyanate in a reactor, add 40 mL of anhydrous butyl acetate and 0.02 g of dibutyltin dilaurate, raise the temperature to 50°C, add 13.6 g of component 2 and stir to react for 7 hours to obtain a flame retardant.

[0045] Example 2 A method for preparing a composite filler comprises the following steps:

[0046] (1) Take 10 mL of tetrabutyl titanate in a reactor, add 4 mL of hydrofluoric acid, stir and mix, place at 205 ° C for 24 hours, filter, wash and dry after the reaction is completed to obtain titanium dioxide nanosheets;

[0047] (2) 2 g of titanium dioxide nanosheets were placed in a reactor, a mixture of 240 mL of ethanol and 120 mL of deionized water was added, and ultrasonic dispersion was performed uniformly. 2 mL of γ-aminopropyltriethoxysilane was added, and the mixture was refluxed at 80 ° C in a nitrogen atmosphere for 6 h. After the reaction was completed, the mixture was filtered, washed, and dried to obtain amino titanium dioxide nanosheets.

[0048] (3) Take 3 g of amino-modified titanium dioxide nanosheets and ultrasonically disperse them in 100 mL of 2 mol / L citric acid solution to obtain a dispersion. Take 370 g of water glass and add 1100 mL of deionized water to mix. Then add 12 mL of ethanol and stir evenly. Heat to 80 °C, add the obtained dispersion, and add dilute sulfuric acid solution to adjust the pH of the system to 6. Add 500 mL of ethanol and stop the reaction when the reaction temperature remains at 80 °C. After the reaction is completed, age for 2 h, centrifuge and wash, and dry to obtain a composite filler.

[0049] Example 3 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 45 parts of nitrile rubber, 22 parts of natural rubber, 7 parts of modified carbon nanotubes prepared in Example 1, 5 parts of composite fillers prepared in Example 2, 3 parts of nano zinc oxide, 2 parts of stearic acid, 1 part of sulfur, and 0.2 parts of accelerator DM.

[0050] The preparation method of the flame retardant and anti-aging cable material comprises the following steps:

[0051] S1, weighing each raw material by weight, putting the nitrile rubber and natural rubber into an internal mixer and plasticating for 3 minutes to obtain a premix;

[0052] S2. Add modified carbon nanotubes, composite fillers, nano zinc oxide and stearic acid to the premix and mix for 5 minutes. Finally, add sulfur and accelerator and mix evenly, then vulcanize at 140°C for 6 minutes. Cool the premix to obtain a flame-retardant and anti-aging cable material.

[0053] Example 4 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 57 parts of nitrile rubber, 32 parts of natural rubber, 10 parts of modified carbon nanotubes prepared in Example 1, 8 parts of composite fillers prepared in Example 2, 4 parts of nano zinc oxide, 3 parts of stearic acid, 2 parts of sulfur, and 0.4 parts of accelerator TMTD.

[0054] The preparation method of the above flame retardant and anti-aging cable material is the same as that in Example 3.

[0055] Example 5 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 68 parts of nitrile rubber, 40 parts of natural rubber, 12 parts of modified carbon nanotubes prepared in Example 1, 10 parts of composite filler prepared in Example 2, 5 parts of nano zinc oxide, 4 parts of stearic acid, 3 parts of sulfur, and 0.5 parts of accelerator TMTD.

[0056] The preparation method of the above flame retardant and anti-aging cable material is the same as that in Example 3.

[0057] Comparative Example 1 A method for preparing modified carbon nanotubes comprises the following steps:

[0058] A. Take 300 mL of concentrated sulfuric acid and 100 mL of concentrated nitric acid in a reactor, add 5 g of carbon nanotubes, disperse evenly by ultrasonication, place at 65 ° C and stir for 4 h, filter, wash and dry after the reaction is completed to obtain acidified carbon nanotubes;

[0059] B. Take 5g of acidified carbon nanotubes in 120mL of anhydrous butyl acetate, disperse them evenly by ultrasonication, raise the temperature to 65°C, add a mixture of 12.2g of flame retardant and 60mL of anhydrous butyl acetate and 0.03g of dibutyltin dilaurate, and react at a constant temperature for 12h. After the reaction is completed, filter, wash and dry to obtain modified carbon nanotubes.

[0060] The preparation method of the flame retardant in step B comprises the following steps:

[0061] B1, take 19.2g of vanillin and 17.8g of anhydrous potassium carbonate and put them into a reactor filled with 300mL of tetrahydrofuran, stir and dissolve, then add 5g of hexachlorocyclotriphosphazene, place at 75°C for reaction for 48h, filter after the reaction is completed, collect the filtrate, evaporate the solvent and wash with ethanol, and vacuum dry to obtain component 1;

[0062] B2, take 4.27g ethanolamine and 80mL ethanol in a reactor, add 10.4g component one, place under reflux reaction at 85°C for 18h, cool to room temperature after the reaction is completed, filter and dry the solid to obtain component two;

[0063] B3. Take 13.2 g of isophorone diisocyanate in a reactor, add 40 mL of anhydrous butyl acetate and 0.02 g of dibutyltin dilaurate, raise the temperature to 50°C, add 13.6 g of component 2 and stir to react for 7 hours to obtain a flame retardant.

[0064] Comparative Example 2 A method for preparing modified carbon nanotubes comprises the following steps:

[0065] A. Take 300 mL of concentrated sulfuric acid and 100 mL of concentrated nitric acid in a reactor, add 5 g of carbon nanotubes, disperse evenly by ultrasonication, place at 65 ° C and stir for 4 h, filter, wash and dry after the reaction is completed to obtain acidified carbon nanotubes;

[0066] B. Take 5 g of acidified carbon nanotubes and ultrasonically disperse them in 200 mL of N,N-dimethylacetamide, add 60 mL of dichlorothionyl and reflux at 80°C for 24 h, then add 4.4 g of p-phenylenediamine and reflux at 125°C for 36 h under nitrogen protection. After the reaction is completed, filter, wash and dry to obtain modified carbon nanotubes.

[0067] Comparative Example 3 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 68 parts of nitrile rubber, 40 parts of natural rubber, 12 parts of modified carbon nanotubes prepared in Comparative Example 1, 10 parts of composite filler prepared in Example 2, 5 parts of nano zinc oxide, 4 parts of stearic acid, 3 parts of sulfur, and 0.5 parts of accelerator TMTD.

[0068] The preparation method of the above flame retardant and anti-aging cable material is the same as that in Example 3.

[0069] Comparative Example 4 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 68 parts of nitrile rubber, 40 parts of natural rubber, 12 parts of modified carbon nanotubes prepared in Comparative Example 2, 10 parts of composite filler prepared in Example 2, 5 parts of nano zinc oxide, 4 parts of stearic acid, 3 parts of sulfur, and 0.5 parts of accelerator TMTD.

[0070] The preparation method of the above flame retardant and anti-aging cable material is the same as that in Example 3.

[0071] Comparative Example 5 A flame retardant and anti-aging cable material comprises the following components in parts by weight: 68 parts of nitrile rubber, 40 parts of natural rubber, 12 parts of modified carbon nanotubes prepared in Example 1, 5 parts of nano titanium dioxide, 5 parts of nano silicon dioxide, 5 parts of nano zinc oxide, 4 parts of stearic acid, 3 parts of sulfur, and 0.5 parts of accelerator TMTD.

[0072] The preparation method of the above flame retardant and anti-aging cable material is the same as that in Example 3.

[0073] Performance Testing

[0074] (1) The cable materials prepared in Example 3-5 and Comparative Example 3-5 were tested for tensile strength and elongation at break according to the national standard GB / T 528-2009, and for tear strength according to the national standard GB / T 529-2008. The flame retardant properties were tested by limiting oxygen index test. The data results are shown in Table 1.

[0075]

[0076] It can be seen from the data in Table 1 that the cable materials prepared in Examples 3-5 of the present invention all have the characteristics of high tensile strength, not easy to break, and good flame retardant properties. Among them, the modified carbon nanotubes added in Comparative Example 3 are not grafted with p-phenylenediamine, and the measured mechanical properties are slightly worse than those of Examples 3-5. The modified carbon nanotubes added in Comparative Example 4 are not grafted with flame retardants, and the measured flame retardant properties are significantly reduced, and the mechanical properties are slightly worse than those of Examples 3-5. In Comparative Example 5, nano titanium dioxide and nano silicon dioxide are simply blended, and the measured mechanical properties are significantly reduced compared with Examples 3-5.

[0077] (2) After the cable materials prepared in Example 3-5 and Comparative Example 3-5 were aged at 100°C for 24 h and 48 h, respectively, the changes in tensile strength and elongation at break were tested, and the anti-aging performance was tested. The data results are shown in Table 2.

[0078]

[0079] It can be seen from the data in Table 2 that the cable materials prepared in Examples 3-5 of the present invention still have high tensile strength and elongation at break after aging for 24h and 48h, indicating that the cable materials have excellent resistance to heat and oxygen aging. In Comparative Example 3, the carbon nanotubes were not treated with grafted antioxidants, and the tensile strength and elongation at break of the cable materials measured after aging decreased significantly.

[0080] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0081] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A flame retardant and anti-aging cable material, characterized in that: The invention comprises the following components by weight: 45-70 parts of nitrile rubber, 20-40 parts of natural rubber, 7-12 parts of modified carbon nanotubes, 5-10 parts of composite fillers, 3-5 parts of nano zinc oxide, 2-4 parts of stearic acid, 1-3 parts of sulfur, and 0.1-0.5 parts of accelerator; The modified carbon nanotubes are prepared by modifying the flame retardant and p-phenylenediamine on the surface of the carbon nanotubes by chemical reaction. The structural formula of the flame retardant is as follows: The composite filler is made by in-situ growing silicon dioxide nanoparticles using titanium dioxide nanosheets as carriers.

2. The flame retardant and anti-aging cable material according to claim 1, characterized in that: The accelerator is one of DM, M, TMTD and D or a mixture of several of them.

3. The flame retardant and anti-aging cable material according to claim 1, characterized in that: The preparation method of the modified carbon nanotubes comprises the following steps: A. Put concentrated sulfuric acid and concentrated nitric acid in a reactor, add carbon nanotubes, disperse them evenly with ultrasound, place them at 50-70°C and stir for 4-6 hours, filter, wash and dry after the reaction is completed to obtain acidified carbon nanotubes; B. Take the acidified carbon nanotubes in anhydrous butyl acetate, disperse them uniformly by ultrasonication, raise the temperature to 60-70°C, add the mixture of flame retardant and anhydrous butyl acetate and dibutyltin dilaurate, react at constant temperature for 8-12 hours, filter, wash and dry after the reaction is completed to obtain a modified intermediate; C. Take the modified intermediate and disperse it in N, N-dimethylacetamide by ultrasonic. Add dichlorothionyl and reflux it at 75-85°C for 18-24 hours. Then add p-phenylenediamine and reflux it at 120-135°C for 24-48 hours under nitrogen protection. After the reaction is completed, filter, wash and dry to obtain modified carbon nanotubes.

4. The flame retardant and anti-aging cable material according to claim 3, characterized in that: In the step B, the mass ratio of the acidified carbon nanotubes to the flame retardant is 1:2-3.

5. The flame retardant and anti-aging cable material according to claim 3, characterized in that: In the step C, the addition ratio of the modified intermediate, thionyl chloride and p-phenylenediamine is 1-5 g: 30-70 mL: 3-5 g.

6. The flame retardant and anti-aging cable material according to claim 3, characterized in that: The method for preparing the flame retardant in step B comprises the following steps: B1. Put vanillin and anhydrous potassium carbonate into a reactor filled with tetrahydrofuran, stir to dissolve, then add hexachlorocyclotriphosphazene, react at 65-80°C for 42-48h, filter after the reaction is completed, collect the filtrate, evaporate the solvent, wash with ethanol, and vacuum dry to obtain component 1; B2, take ethanolamine and ethanol into a reactor, add component one, place under reflux reaction at 75-90°C for 12-24h, cool to room temperature after the reaction is completed, filter and dry the solid to obtain component two; B3. Take isophorone diisocyanate in a reactor, add anhydrous butyl acetate and dibutyltin dilaurate, raise the temperature to 40-55°C, add component 2 and stir to react for 5-8 hours to obtain a flame retardant.

7. The flame retardant and anti-aging cable material according to claim 6, characterized in that: In step B2, the molar ratio of ethanolamine to component 1 is 6.6-10:

1.

8. The flame retardant and anti-aging cable material according to claim 6, characterized in that: The molar ratio of isophorone diisocyanate to component 2 in step B3 is 1-2:

1.

9. The flame retardant and anti-aging cable material according to claim 1, characterized in that: The preparation method of the composite filler comprises the following steps: (1) Tetrabutyl titanate is placed in a reactor, hydrofluoric acid is added, stirred and mixed, and reacted at 195-210° C. for 18-24 hours. After the reaction is completed, the reaction is filtered, washed and dried to obtain titanium dioxide nanosheets; (2) Put titanium dioxide nanosheets in a reactor, add a mixture of ethanol and deionized water, disperse them evenly by ultrasonication, add γ-aminopropyltriethoxysilane, and reflux them at 70-85°C in a nitrogen atmosphere for 5-7 hours. After the reaction is completed, filter, wash, and dry to obtain amino titanium dioxide nanosheets; (3) Aminated titanium dioxide nanosheets are ultrasonically dispersed in a 1.5-2 mol / L citric acid solution to obtain a dispersion. Water glass is added to deionized water and mixed. Then, ethanol is added and stirred evenly. The temperature is raised to 75-85°C, the obtained dispersion is added, and a dilute sulfuric acid solution is added dropwise to adjust the pH of the system to 5-6. Ethanol is added and the reaction is stopped when the reaction temperature is maintained at 75-85°C. After the reaction is completed, the composite filler is aged, centrifuged, washed, and dried to obtain the composite filler.

10. The method for preparing the flame-retardant and anti-aging cable material according to claim 1, characterized in that: The following steps are involved: S1. Weigh each raw material by weight, put the nitrile rubber and natural rubber into an internal mixer and plasticize for 2-3 minutes to obtain a premix; S2. Add modified carbon nanotubes, composite fillers, nano zinc oxide and stearic acid to the premix and mix for 3 to 5 minutes. Finally, add sulfur and accelerator and mix evenly. Vulcanize at 120 to 160°C for 5 to 10 minutes. Cool the premix to obtain a flame retardant and anti-aging cable material.

Citation Information

Patent Citations

  • Method for preparing hexachlorocyclotriphosphazene

    CN102070672A

  • Composite mica copper sheath high-performance fireproof cable for high-speed rail

    CN118994768A